Three cases of Zika virus imported in Italy: need for a clinical awareness and evidence-based knowledge. Issue 1 (December 2016) - Nicastri, Emanuele; Pisapia, Raffaella; Corpolongo, Angela; Fusco, Francesco; Cicalini, Stefania; Scognamiglio, Paola; Castilletti, Concetta; Bordi, Licia; Di Caro, Antonino; Capobianchi, Maria; Puro, Vincenzo; Ippolito, Giuseppe
Abstract Background Since early 2015, a large epidemic of Zika Virus (ZIKV) is spreading across South and Central America. An association between congenital neurological malformations (mainly microcephaly), other neurological manifestations such as Guillain-Barrè Syndrome, and ZIKV infection is suspected. Case presentation Three confirmed cases of ZIKV in travelers returning from Brazil between May 2015 and January 2016 are described. All patients had mild symptoms with no neurological complications. Conclusions An increasing awareness among clinicians about this emerging disease is advisable, both for the need to provide correct additional information to the patients and to travelers, with a special focus on pregnant women, and for the presence of the competent vector in Southern Europe.